Sensors and Transducers for Lava Flood Detection: Systematic Literature Review - Iswanto, Iswanto; John Minto; Esraa Abdellatif Hammouda; Mohamed Yusuf Hassan; Abdikani Yusuf Abdulle (Sunan Kalijaga Journal of Physics, 2022)
Disasters always come suddenly, becoming a natural phenomenon that humans face. One of the natural disasters is a lava flood, which is a collection of lava released by a volcano and reaches the lower surface with the help or encouragement of rainwater. The impact of lava floods has a high risk because the material it carries can cause damage and has the potential to cause death, injury, illness, life at risk, loss of security, displacement, damage or loss of property, and disruption of community activities, so an early warning system is needed. can provide accurate data about the time of the disaster. To overcome digital sophistication, tools have been created in the form of sensors and transducers for lava flood detection. The aim of this research is to examine sensors and transducers for lahar flood detection. This research uses a systematic literature review using Preferred Reporting Items for Systematic Reviews (PRISMA). The results of article screening and selection found 77 potential articles that met the inclusion criteria. The results of the research show that the development of sensors and transducers has begun to create a lot of lahar flood detection tools through artificial intelligence based on the internet of thought which uses sensors and transducers inside and optimization of sensors and transducers for lahar flood detection must be done by setting the point of detection tools for use in various flood-prone locations. lava, so that detection of lava floods can be known before a disaster occurs.